PANDAS, Tics and OCD, and Immunotherapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Thirty children with severe, streptococcal-triggered exacerbations of tics or obsessive compulsive disorder (OCD) were treated with plasma exchange (5 in 2 weeks), intravenous immunoglobulin (IVIG, 1 g/kg daily on 2 consecutive days), or placebo saline solution, randomly assigned, in a study at the National Institutes of Health, Bethesda, MD.